DESIGN, OPTIMIZATION AND EVALUATION OF IBUPROFEN FAST DISSOLVING TABLETS EMPLOYING STARCH PHTHALATE-A NOVEL SUPERDISINTEGRANT - KUMAR, R. SANTOSH; ANNU, KUMARI; LATHA, B. KUSUMA; MALLIKA, T. (International Journal of Current Pharmaceutical Research, 2019)
Objective: The objective of the present research was to prepare starch phthalate (a novel super disintegrant) and to optimize and formulate ibuprofen fast dissolving tablets employing 23factorial design using starch phthalate as super disintegrant. Methods: Drug excipient compatibility studies like Fourier-transform infrared spectroscopy (FTIR) and thin-layer chromatography (TLC) studies were carried out to check the drug interaction between ibuprofen and starch phthalate. Direct compression method was used for tablet preparation. Prepared tablets were then evaluated for hardness, friability, drug content, disintegration time, water absorption and wetting time, in vitro dissolution studies. Response surface plots and contour plots were also plotted to know the main effects and interaction effects of independent variables (starch phthalate (A), croscarmellose sodium (B) and crospovidone (C)) on dependent variables (disintegration time and drug dissolution efficiency in 1 minute) and stability studies were also done. Results: Tablets of all formulations were of good quality concerning drug content (100±5%), hardness (3-6 kg/cm2), and friability (less than 0.16%). In all formulations, formulation F5 found to be optimized formulation with least disintegration time 20±0.28 seconds, less wetting time 09±0.12 seconds and enhanced dissolution rate in one minute, i.e., 91.95±0.22 as compared to other formulation. Conclusion: From the research, it was concluded that on combination with crospovidone, starch phthalate enhanced the dissolution efficiency of the drug. Hence, starch phthalate can be used as a novel disintegrant in the manufacturing of fast dissolving tablets.